Spatial Behavior Analysis of Covid-19 Health Protocol Violation By Traders Along Pasar Ciluar Street - Widis Aryasuta Ragawardhana; Widyawati Sumadio; Ahmad Zubair (Jurnal Pembangunan Wilayah dan Kota, 2021)
Each individual has basic knowledge in decision-making because the information is not only obtained from the setting of his environment, but also the mass media, hence the differences in behavior in the environment, society, and culture of a space. COVID-19 is a newly discovered pandemic disease known as the acute respiratory disease SARS-CoV-2 virus. The search for basic necessities during a pandemic is very crucial. New regulations are made restricting all trading activities in traditional markets. This research was conducted in a traditional market located along Pasar Ciluar Street, Sukaraja District, Bogor Regency. Regulations were made by the West Java Provincial Government, such as the New Habit Adaptation program as a manifestation of the guidelines from WHO, in addition to the Bogor District Head Regulation Number 35 of 2020 concerning health protocols for economic areas requiring employees to wear masks, disinfect goods to be sold, and others. Many traders do not adhere to protocols, increasing the vulnerability of the spread of COVID-19. This study aims to examine the patterns and distribution of health protocols as well as behavioral motivations carried out by traders in health protocols. Using a qualitative approach, the place-centered mapping method is used for spatial analysis. The results of this study recount the behavioral spatial with a linear distribution pattern along Pasar Ciluar Street and the motivation of traders who violate the required health protocols.